RETRACTED: Development of a new approach to ensuring the economic security of Uzbekistan agricultural enterprises - Uktamov Khusniddin; Abdullayeva Shakhnoza; Imomov Jamshidxon; Rejapov Xayrillo (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001